Analysis of the enterprise's availability of fixed assets and their technical condition ("Journal "U". Economy. Management. Finance.", 2025)
The article analyzes the shoe factory's availability of fixed assets, their structure, movement, and technical condition. A factor analysis of capital productivity and capital profitability is performed, key factors determining their dynamics are identified, and directions for improving the efficiency of fixed asset management are proposed.
Keywords: fixed assets; capital productivity; capital profitability; technical condition; wear and tear; capital equipment; factor analysis